Learning English mediated by Kahoot: Insights from the Indonesian EFL instructors - Moh. Arif Mahbub (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
Now, EFL pedagogical practices have gradually transformed from traditional classrooms into digital learning. Within this context, mobile devices have now been considered as an auspicious medium for future learning. This study investigated how EFL instructors from different secondary education institutions viewed the in-class use of Kahoot in English-language classrooms. To this end, they were invited to fill a 13-items web-based questionnaire covering several categories: factual, behavioral, and attitudinal. Twenty-seven (n=27) Indonesian EFL instructors in secondary education at both public and private high schools mostly located in East Java, Indonesia, voluntarily participated in this present study by completing the online survey. The results indicated that participants mostly demonstrated positive feelings toward the utilization of Kahoot in EFL classrooms. It showed that Kahoot was perceived as a promising software application to enhance the English-language learning process. To explore the effectiveness of this online game-based platform, more future-related research with large-scale participants in broader geographic regions should be carried out in this area.